Born preterm: a public health issue - Pinto, Filomena (2019)
ABSTRACT - Background: Prematurity accounts for about 10.6% of neonates worldwide and tends to increase as does survival from lower gestational ages. Summary: The importance of preterm birth in public health stems from its link to infant and under-5 mortality, morbidity, and its economic impact. In both the short and long term, preterm birth consequences are inversely related with gestational age and carry a higher risk of mortality and morbidity with neurodevelopmental, sensorial, cognitive and physical health disturbances. Individuals needing lifelong support pose challenges to the responsiveness of health services and community systems. Public health can be decisive in prematurity prevention, providing data to policy-makers and reducing modifiable risk factors. This paper focuses on the long-term consequences of preterm birth and possible public health measures to tackle them. Key Messages: Addressing social determinants of health can have the highest impact on prematurity outcomes.